(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Man’s natural ability to tell stories was not hidden from literary critics’ speculative eyes. Oral and written storytelling has been around for thousands of years. The fascination with ontological and epistemological questions regarding being and the unknown has prompted the man to use his imagination motor to explore and dwell simultaneously in both real and fictional worlds, actual and virtual ones. This article is an attempt to connect different interpretations of trans-textualized hypertexts or retellings that have emerged as a result of the contemporary movements of structuralism and poststructuralism in the light of Gerard Genette’s narrative theory, in order to emphasize the dialectic of assumptions and positive expectations. Structuralist narrative theories prove inapt to justify the thematic modifications of the hypertexts created as the result of trans fictionality. To meet the aim of the study the descriptive method is utilized, which seeks to explore the narratological dimensions of the four retellings above of the Odyssey, based on the structuralist view. Considering the results, narratological reading based on the overall structure of a narrative, or langue, cannot justify the changes that hypersexuality is responsible for, and the reading has to be in line with the parole, or the specific style of each hypertext.